2019
DOI: 10.3390/su11185094
|View full text |Cite
|
Sign up to set email alerts
|

Research Collaboration of Austrian and Indian Teenagers in the Context of Education for Sustainable Development

Abstract: Today’s environmental challenges have been determined and exacerbated by human behavior. It is imperative that education develops learning-settings that enable students to make their individual lifestyles more sustainable. The aim of this paper is to examine the effect of the research-education-collaboration ‘AustrIndia-4QOL’ (Teenagers from Austria and India Perform Research on Quality of Life) on the teenagers’ awareness of the importance of environmental aspects in regards to quality of life, and on their w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Our results showed that secondary school education affects learners' EA, and so can primary schools [94,100] and higher education [101], as well as other institutions that implement (in)formal ESD [99] and learning opportunities in everyday life [102]. As the term education in ESD already indicates, ESD is a long-term process and cannot be achieved by single interventions [103,104]. To implement ESD, the teachers play a crucial role [99,103,105,106].…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed that secondary school education affects learners' EA, and so can primary schools [94,100] and higher education [101], as well as other institutions that implement (in)formal ESD [99] and learning opportunities in everyday life [102]. As the term education in ESD already indicates, ESD is a long-term process and cannot be achieved by single interventions [103,104]. To implement ESD, the teachers play a crucial role [99,103,105,106].…”
Section: Discussionmentioning
confidence: 98%
“…They proposed that social networks play a particularly important role in policy domains such as climate change education and education for sustainable development, which are best described as multi-level and multi-actor governance. Dür and Keller, [68] investigated the impact of the research-education collaboration 'AustrIndia-4QOL' (Teenagers from Austria and India Perform Quality of Life Research) on teenagers' awareness of the importance of environmental aspects in terms of quality of life, as well as their willingness to act towards more sustainable lifestyles. The findings suggest that conducting education for sustainable development necessitates long-term educational engagement and that unforeseen consequences cannot be ruled out.…”
Section: Cluster 3: Educationmentioning
confidence: 99%
“…The findings suggest that conducting education for sustainable development necessitates long-term educational engagement and that unforeseen consequences cannot be ruled out. [68]…”
Section: Cluster 3: Educationmentioning
confidence: 99%
“…In recent years, researchers have tried to explain four main areas. First, the definition of sustainability (Merle et al, 2019;Orna-Montesinos, 2015;Pasquaré and Oppizzi, 2012); second, the tendency (Wei et al, 2015;Boykoff, 2010;Xiong et al, 2016); third, the increase of willingness to act on environmental (Guo and Marinova, 2011;Dür and Keller, 2019) and the last main area, the differences of prioritisations on sustainabilityrelated issues in different parts of the world (Schmidt et al, 2013;Barkemeyer et al, 2013). Most of these publications consider newspaper articles as their source of analysis.…”
Section: Introductionmentioning
confidence: 99%